Targeting social safety nets using proxy means tests: Evidence from Egypt’s Takaful and Karama program - Kurdi, Sikandra; Breisinger, Clemens; ElDidi, Hagar; El-Enbaby, Hoda; Gilligan, Daniel O.; Karachiwalla, Naureen (International Food Policy Research Institute, 2018)
Chapter 10 uses Egypt as a case study to examine the effectiveness of proxy means test (PMT) targeting. Targeting effectiveness is defined in terms of the ability of the program to enroll beneficiaries from the lowest two quintiles of the expenditure distribution. The authors also consider the social costs of implementing PMT in a context where administrative capacity to explain the targeting mechanism to the public is imperfect.